Emotion awareness and somatic complaints in preadolescence: The mediating role of coping strategies. Issue 3 (11th December 2017) - Mazzone, Angela; Camodeca, Marina
Abstract: Somatic complaints are frequent among preadolescents with impaired emotion awareness and maladaptive coping strategies. In addition, coping strategies in response to stressful events have been suggested to affect the association between emotion awareness and somatic complaints. However, empirical support for this assumption is missing. In this study, we examined the extent to which emotion awareness and coping contributed uniquely to somatic complaints and the indirect effect of emotion awareness on somatic complaints through coping strategies, among preadolescent boys and girls. Self‐reports were administered to 265 preadolescents (137 boys; M age  = 12.04) to investigate somatic complaints, emotion awareness, and coping strategies to deal with peer victimization. A subsample ( N  = 97) was assessed after a 12‐month time‐span. Cross‐sectional results indicated that more somatic complaints were associated with less emotion awareness and problem‐solving and with more internalizing and externalizing coping. Poor emotion awareness was indirectly associated with somatic complaints through internalizing for boys and through distraction, externalizing, and internalizing for girls. Emotion awareness was longitudinally associated with somatic complaints through distraction for boys. Overall, findings suggested that less emotion awareness was associated with more maladaptive coping strategies, which in turn contributed to more somatic complaints. Implications for research and intervention are discussed. Highlights: The present study investigated the associations between somatic complaints, emotion awareness, and coping strategies among preadolescent boys and girls. Self‐report data were collected. Results showed that poor emotion awareness was indirectly associated with somatic complaints through internalizing for boys and through distraction, externalizing, and internalizing for girls. Improving emotion awareness and effective coping strategies may reduce somatic complaints among preadolescents and offer them a better social and psychological adjustment.